Dung-Associated Insects: Ecological Roles and Potential Benefits in Agricultural - Nur Ain Izzati Mohd Zainudin; Subramaniam, Sivagami; Azrizal-Wahid, Noor (Universitas Andalas, 2025)
Dung-associated insects, often referred as coprophagous insects and detritivores, help break down organic matter, returning essential nutrients to the soil and promoting plant growth. Their activities not only enhance soil structure and fertility but also aid in pest control by reducing the populations of parasites and pathogens associated with animal waste. Understanding the complex relationships between dung-inhabiting insects and their environment highlights the crucial role these creatures play in maintaining ecological balance. These insects facilitate nutrient cycling and contribute to overall biodiversity. It plays a crucial role in promoting healthy ecosystems, as its presence can lead to improved soil health and increased agricultural productivity. Implementing integrated pest management practices that encourage the presence of dung-inhabiting insects can further enhance their role in sustainable agriculture, promoting a balanced ecosystem where both crops and beneficial organisms grow well. This approach not only promotes biodiversity but also enables farmers to adopt more environmentally friendly practices that contribute to long-term agricultural resilience.